2. Simplify these expressions
a 6ab + (-3x) + 2ab
b. 12x + 4y + (-3x)
c 6w + (-2y) + 3w
d 4abc + (-9abc) + 10d

Respuesta :

Answer:

Step-by-step explanation:

a 6ab + (-3x) + 2ab

we have  6ab + 2ab - 3x = 8ab - 3x

b. 12x + 4y + (-3x)

we have  12x - 3x + 4y = 9x + 4y

c 6w + (-2y) + 3w

we have  6w + 3w - 2y = 9w - 2y

d 4abc + (-9abc) + 10d

we have 4 abc - 9abc + 10d = - 5abc + 10d

Here for you.

Answer:

a. 6ab + (-3x) + 2ab we have  6ab + 2ab - 3x = 8ab - 3x

b. 12x + 4y + (-3x) we have  12x - 3x + 4y = 9x + 4y

c 6w + (-2y) + 3w we have  6w + 3w - 2y = 9w - 2y d 4abc + (-9abc) + 10

d we have 4 abc - 9abc + 10d = - 5abc + 10d  

Step-by-step explanation: